MISLEADING PERCEPTIONS WITH ETHNIC MINORITIES: THE CASE OF PONTIAC GREEKS IN CYPRUS - Gregory Neocleous; Menelaos Apostolou; Stefanos Spaneas (European Scientific Journal, ESJ, 2015)
Immigration policy in Cyprus was largely formulated in the 1990s, with the intent to meet the labour shortages as a result of the growth in tourism. Consequently, a large number of Pontiacs (or Pontic-Greeks) of Greek origin from the Caucasus region migrated to the Republic of Cyprus. Today, the overall number of Pontiacs is estimated to be a total of about 20,000, out of which 10,000-12,000 are living in the Municipality of Paphos. This paper aims to highlight the importance of the use of social services by Pontic-Greeks as part of their integration into the local society. Ethnic Pontic-Greeks in Paphos were asked to describe their current living conditions and their relationships with the local society and the use of social services, such as community kindergartens, children after-school services, nursing homes, senior citizens centres, and social welfare agencies. Τhe analysis articulated an underuse or no use at all of social services by PonticGreeks, mainly because they are not aware of these services or they hesitate to use them because they do not feel comfortable with the dominant population group; an issue that is an impediment to their social integration.